2012
DOI: 10.1136/gutjnl-2012-302529
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan impairs vascular function and drug delivery in a mouse model of pancreatic cancer

Abstract: ObjectivePancreatic ductal adenocarcinoma (PDA) is characterised by stromal desmoplasia and vascular dysfunction, which critically impair drug delivery. This study examines the role of an abundant extracellular matrix component, the megadalton glycosaminoglycan hyaluronan (HA), as a novel therapeutic target in PDA.MethodsUsing a genetically engineered mouse model of PDA, the authors enzymatically depleted HA by a clinically formulated PEGylated human recombinant PH20 hyaluronidase (PEGPH20) and examined tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
930
6
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 918 publications
(971 citation statements)
references
References 37 publications
25
930
6
10
Order By: Relevance
“…We have recently shown that pharmacological inhibition of SHH by IPI-926 and the enzymatic degradation of HA by PEGPH20 improved chemotherapy delivery either through increased mean vessel density and stromal depletion or by reexpansion and endothelial fenestration formation of blood vessels, respectively (12,16). Here we investigated whether increased accumulation of active gemcitabine triphosphate (2′,2′-difluorodeoxycytidine-5′-triphosphate; dFdCTP) without additional modifications of the tumor vasculature or stromal composition would be sufficient to improve therapeutic response in tumor-bearing KPC mice.…”
Section: Isolated Elevation Of Active Gemcitabine Triphosphate Does Notmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that pharmacological inhibition of SHH by IPI-926 and the enzymatic degradation of HA by PEGPH20 improved chemotherapy delivery either through increased mean vessel density and stromal depletion or by reexpansion and endothelial fenestration formation of blood vessels, respectively (12,16). Here we investigated whether increased accumulation of active gemcitabine triphosphate (2′,2′-difluorodeoxycytidine-5′-triphosphate; dFdCTP) without additional modifications of the tumor vasculature or stromal composition would be sufficient to improve therapeutic response in tumor-bearing KPC mice.…”
Section: Isolated Elevation Of Active Gemcitabine Triphosphate Does Notmentioning
confidence: 99%
“…In addition, megadalton glycosaminoglycan hyaluronan (HA) is profusely found in the ECM of murine and human PDA and maintains a high interstitial fluid pressure, thus compressing blood vessels (13)(14)(15). We and others have recently provided evidence that enzymatic degradation of HA by PEGPH20 significantly increased vessel patency and perfusion without increasing the density of tumor vessels, resulting in increased active gemcitabine levels in the tumor (15,16). Both the antismoothened and hyaluronidase therapeutic approaches resulted in transient antitumor responses and prolonged survival in the KPC mouse model.…”
mentioning
confidence: 99%
“…The authors found that when combined with gemcitabine, PEGPH20 inhibited tumor growth and prolonged survival vs. gemcitabine alone in mice models. [33] A summary of antifibrotic therapies and their respective mechanisms of action are listed in Table 2.…”
Section: Drug Name Mechanism Of Action Referencementioning
confidence: 99%
“…[33] A study by Provenzano et al assessed the possibilities for using enzymes to target the stroma with hopes to increase efficacy of chemotherapy. [34] The authors used PEGPH20 to deplete hyaluronan in mice PDAC cells.…”
Section: Drug Name Mechanism Of Action Referencementioning
confidence: 99%
See 1 more Smart Citation